2021
DOI: 10.1002/hipo.23333
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfield‐specific Homer1a expression is triggered by learning‐facilitated long‐term potentiation and long‐term depression at medial perforant path synapses

Abstract: Learning about general aspects, or content details, of space results in differentiated neuronal information encoding within the proximodistal axis of the hippocampus.These processes are tightly linked to long-term potentiation (LTP) and long-term depression (LTD). Here, we explored the precise sites of encoding of synaptic plasticity in the hippocampus that are mediated by information throughput from the perforant path. We assessed nuclear Homer1a-expression that was triggered by electrophysiological induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 96 publications
(207 reference statements)
1
20
0
Order By: Relevance
“…The hippocampal CA1 region plays an important role in the learning about microscale item-place configurations (Kemp and Manahan-Vaughan, 2004;Hagena and Manahan-Vaughan, 2011;Hoang et al, 2018), and the microscale and macroscale behavioral paradigms used in the current study trigger both synaptic plasticity and somatic IEG expression in distinct subcompartments of the hippocampus (Hoang et al, 2018;Hoang and Manahan-Vaughan, 2021). Interestingly, it has been reported that a direct projection from neurons in the superficial layers of the PRC to the CA1 region and more strongly to the subiculum of the hippocampus exists (Naber et al, 1999;Furtak et al, 2007;Agster and Burwell, 2013;Suter et al, 2013).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The hippocampal CA1 region plays an important role in the learning about microscale item-place configurations (Kemp and Manahan-Vaughan, 2004;Hagena and Manahan-Vaughan, 2011;Hoang et al, 2018), and the microscale and macroscale behavioral paradigms used in the current study trigger both synaptic plasticity and somatic IEG expression in distinct subcompartments of the hippocampus (Hoang et al, 2018;Hoang and Manahan-Vaughan, 2021). Interestingly, it has been reported that a direct projection from neurons in the superficial layers of the PRC to the CA1 region and more strongly to the subiculum of the hippocampus exists (Naber et al, 1999;Furtak et al, 2007;Agster and Burwell, 2013;Suter et al, 2013).…”
Section: Discussionmentioning
confidence: 77%
“…The hippocampal dentate gyrus region engages in macroscale item-place encoding (Kemp and Manahan-Vaughan, 2008; Hoang et al, 2018Hoang et al, , 2021. This prompts the question as to whether this process may be supported by macroscale item encoding in area 35.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that highly localized gene encoding occurs in the hippocampus during the strengthening of synaptic plasticity by spatial learning (Hoang et al, 2021 ). By contrast, strong afferent protocols that induce highly robust forms of LTP and LTD result in generalized and indiscriminate immediate early gene encoding across the hippocampus (Hoang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that highly localized gene encoding occurs in the hippocampus during the strengthening of synaptic plasticity by spatial learning (Hoang et al, 2021 ). By contrast, strong afferent protocols that induce highly robust forms of LTP and LTD result in generalized and indiscriminate immediate early gene encoding across the hippocampus (Hoang et al, 2021 ). In this context, it is interesting to note that slow-onset potentiation that is induced by learning activity is impaired in mice that either lack D2R, or undergo local silencing of the receptor in the CA1 region (Espadas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%